Global Publication Trends in Second Language Willingness to Communicate Research: A Bibliometric Analysis From 2020 to 2025 - Taufik Akbar Azwar; Dedi Jasrial; Thanin Sengrat (Universitas Islam Negeri (UIN) Sultanah Nahrasiyah Lhokseumawe, 2026)
This present research aims to conduct a comprehensive bibliometric analysis and visual mapping of research trends and directions on second language willingness to communicate (L2 WTC) studies published between 2020 and 2025. Biblioshiny was used to conduct the bibliometric analysis, and VOSviewer for network visualization map. A total of 631 articles were collected from the Scopus database. The findings revealed a steady publication growth each year, with the highest rise in 2025. The three most productive and impactful authors included Lee, J.S., MacIntyre, P.D., and Peng, J-E. The most productive journal is the Language Teaching Research. China became the leading nation in both research production and international research collaboration. Finally, the keyword analysis showed seven clusters, with “WTC” as the largest node. Five emerging topics were identified, including emerging technologies, positive psychology, emotional regulations, intercultural and international orientations, and informal digital learning. Yet, scholarly interest around the foundational elements of L2 WTC, including individual and situational variables, remains relevant. Following the findings, implications for L2 teachers and future researchers are proposed in this study.